Use of the figure of the humor stereotype programs in brazilian tv: a linguistic-discursive analysis about the effects of sense of humor in humorous gender (Research, Society and Development, 2016)
Stereotypes are forms of linguistic-discursive assumptions more or less standard circulating in society, guided by culture. In general, they appear in the practices of humor to be a mode in which the jocular allows speech is free and open to any semantic placements. In this sense, the stereotypes include the humorous ways in order to portray the ridiculousness or different in many respects. The importance of this study is by investigation of how these stereotypes show the mood at the same time consolidate even as prejudices in society. Therefore, he went to an investigation for understanding the construction and dissemination of stereotypes and the influence of these in the production of humor of the national media, on television sitcoms, and show the influence of this image in Brazilian society. As a theoretical framework, we used the semantic theory of humor Raskin (1944), the postulates of Bobbio (2011), referring to the various types of prejudices, defending the idea that there are two forms of prejudice: the individual and the collective, the latter being the research object of this study, it is intended to explain why humor is built on some stereotypes that are shared socially and discourse of media as persuasion mechanism in the work of Charaudeau (2006). transcripts of television programs and discursive analysis were made to verify the incidence of humorous supported critical in stereotypical molds. As a result, it can be seen that in all programs selected the presence of the stereotype was present considering models: poor, gay, stammering, fat and disabled. There was thus a socially constituted model within the classic stereotypes, which concluded that humor is also surrounded by prejudice, a reflection of the view of society, that although notice these models, laugh and have fun on such conditions.